ChemInform Abstract: Oximinoalkylamines as Ligands for Cu‐Assisted Azide—Acetylene Cycloaddition. Issue 13 (March 2016) - Semakin, Artem N.; Agababyan, Daniil P.; Kim, Sohee; Lee, Sangyoon; Sukhorukov, Alexey Yu.; Fedina, Ksenia G.; Oh, Jinho; Ioffe, Sema L.
Abstract: The oxime group may be considered as an efficient binding motif for the design of ligands to accelerate the Cu‐assisted azide—acetylene cycloaddition reaction.